AURA MASYARAKAT MENGHADAPI COVID-19 DALAM ASPEK ANALISIS SWOT DI LOKASI KELOMPOK 17-18 KKNt UNMER PASURUAN TAHUN 2020 - Bambang Sutikno; Sri Hastari; Yufenti Oktafiah (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to create alternative strategies that must be carried out by policy makers and mass organizations or NGOs as well as the community in an effort to prevent the spread and cutting of the Covid-19 cycle at the UNMER Pasuruan Community Service Center 2020 location in Rejoso District, Pasuruan Regency. This type of research is descriptive quantitative. The purpose of the SWOT analysis is to adjust the strengths and weaknesses possessed by the opportunities and threats faced by the government and mass organizations or NGOs and the community in order to create a healthy and ideal living environment that is free from the shackles of Covid-19.